Experience-Based Value Innovation in Culinary MSMEs: A Blue Ocean Strategy Case Study of Bubur Bakar Claypot Teman Setia Surabaya - Cindi Fatikah; Jojok Dwiritjahjono (Jurnal Investasi Islam, 2026)
The food and beverage (F&B) industry is increasingly characterized by intense competition and market homogenization, encouraging culinary MSMEs to create value beyond product quality and price competition. This study aims to analyze the implementation of Blue Ocean Strategy (BOS) in shaping experience-based value innovation at Bubur Bakar Claypot Teman Setia Surabaya. This study employed a qualitative case study approach through interviews, observations, and documentation. Data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña. The findings indicate that the implementation of BOS is not oriented toward price competition, but toward the creation of multisensory and emotional consumption experiences through the use of claypot, live cooking concepts, smoky aromas, interactive service, and customer engagement. The ERRC Grid analysis reveals a reconstruction of competitive factors by reducing the emphasis on price competition while increasing sensory experience, service interaction, and customer engagement. In addition, the Strategy Canvas analysis shows that the company possesses a distinct value curve compared to conventional porridge businesses. The findings also indicate that experience-based differentiation can create value innovation, although it is accompanied by operational challenges related to service coordination complexity and service consistency.